Synthesis of CoFe2O4nanoparticles by refluxing-calcining combination for using as magnetic resonance imaging agents - Sudarat Sitthichai (2018)
Copyright © 2017 American Scientific Publishers All rights reserved. CoFe2O4magnetic nanoparticles (MNPs) were successfully co-precipitated by refluxing method and followed by high temperature calcination. Phase, morphology, oxidation state and magnetic property were characterized by a selected area electron diffraction (SAED) technique, a transmission electron microscope (TEM), a scanning electron microscope (SEM), an X-ray photoelectron spectrometer (XPS), a Fourier transform infrared (FTIR) spectrometer, a Raman spectrophotometer and a vibrating sample magnetometer (VSM). The CoFe2O4MNPs were also studied for magnetic resonance imaging (MRI). They were found to have very high r2relaxivity of 1,313 mM−1· s−1and were able to be used for MRI application with very good contrast.